Inadequate Neuraxial Anesthesia in Patients Undergoing Elective Cesarean Section: A Systematic Review. Issue 1 (22nd March 2023) - Patel, R.; Kua, J.; Sharawi, N.; Bauer, M.E.; Blake, L.; Moonesinghe, S.R.; Sultan, P.
Abstract : ( Anaesthesia . 2022;77:598–604) While neuraxial anesthesia (NA) is often a common and safe form of anesthesia, it does not always properly manage pain, especially during cesarean delivery (CD). Previous studies determining the rate of inadequate NA during CD have small sample sizes and different diagnostic criteria, resulting in a wide range of reported rates of neuraxial failure, from 1.7% to 19.7%. Understanding the incidence and risks associated with failed NA would provide valuable data to guide clinicians in counseling their patients, to prompt earlier recognition and intervention if NA failure occurs, and to direct future research. By systematic review, this study sought to investigate the rate of failed neuraxial block during CD as defined by the need to repeat NA or abandon NA in favor of general anesthesia, administer intraoperative IV analgesia (excluding benzodiazepines), or supplement the epidural during the procedure. Secondary outcomes included comparing neuraxial mode failure rates and determining the rates of conversion to general anesthesia.